R‐DHA‐oxaliplatin (R‐DHAOx) versus R‐DHA‐cisplatin (R‐DHAP) regimen in B‐cell lymphoma treatment: A eight‐year trajectory study. (11th May 2020) - Lacout, Carole; Orvain, Corentin; Seegers, Valérie; De Vries, Manon; Mercier, Mélanie; Farhi, Jonathan; Clavert, Aline; Thepot, Sylvain; Moles, Marie‐Pierre; Ifrah, Norbert; Hunault‐Berger, Mathilde; Tanguy‐Schmidt, Aline
Abstract: Background: The R‐DHAP regimen (rituximab, cisplatin, dexamethasone, and high‐dose cytarabine) is standardly used to treat relapsed Non‐Hodgkin lymphoma (NHL). Despite scarce data, cisplatin is frequently substituted with oxaliplatin (R‐DHAOx) to avoid nephrotoxicity. We compared nephrotoxicity of cisplatin and oxaliplatin based on creatinine‐based trajectory modeling. Methods: All patients with NHL treated by R‐DHAP or R‐DHAOx in Angers hospital between January 01, 2007, and December 31, 2014, were included. Patients received cisplatin 100 mg/m 2 or oxaliplatin 130 mg/m 2 (d1) with cytarabine (2000 mg/m 2, two doses, d2), dexamethasone (40 mg, d1‐4), and rituximab (375 mg/m 2, d1). Creatinine levels were recorded before each cycle. Individual profiles of trajectories were clustered to detect homogeneous patterns of evolution. Results: Twenty‐two patients received R‐DHAP, 35 R‐DHAOx, 6 switched from R‐DHAP to R‐DHAOx due to nephrotoxicity. Characteristics of patients were similar between two groups. Patients receiving R‐DHAP experienced more severe renal injury than patients receiving R‐DHAOx (68% vs. 7.7%, P  < .001). Two homogeneous clusters appeared: cluster A, with a majority of R‐DHAOx (32, 91.4%), was less nephrotoxic than B, with a majority of R‐DHAP (19, 86.4%), with a decreased average serum creatinine level ( P  < .0001). There were no other differences between clusters. Conclusions: Our study confirms that R‐DHAOx regimen causes less nephrotoxicity than R‐DHAP regimen.